Incidence, trends and patterns of female breast, cervical, colorectal and prostate cancers in Antigua and Barbuda, 2017–2021: a retrospective study - Andre A. N. Bovell; Thendo Ramaliba; Sekeena O. Goodwin; Joycelyn C. Phillip; Jabulani Ncayiyana; Themba G. Ginindza (BMC Cancer)
Abstract Background Globally, estimates of cancer cases and deaths have increased since 2018, particularly in Latin America and Caribbean countries. In Antigua and Barbuda, understanding the burden of common cancers such as female breast, cervical, colorectal and prostate cancers is critical. This study aimed to assess the incidence, trends, and patterns of these four cancers from 2017 to 2021. Methods Using a retrospective observational study design, information on these cancers was abstracted from medical records at four key study sites in Antigua and Barbuda. Estimates of age-specific and age-standardized incidence were determined using direct standardization. The KeyFitz method was used to derive standard errors and confidence intervals. Derived estimates were employed to analyze trends and Joinpoint regression modeling was used to determine annual percentage change. Results Between 2017 and 2021, 391 cases of female breast (41.7%), cervical (10.2%), colorectal (20.2%) and prostate (27.9%) cancers were diagnosed. Overall mean age at presentation was 61.5 (± 12.9) years, ranging from 24 to 94 years, age-standardized incidence rate 65.2 (95% CI: 58.7–71.6) per 100,000 population. Age-standardized incidence rate for female breast cancer was 49.9 (95% CI: 42.2–57.8), annual percentage change in incidence a low of -0.2%. Prostate cancer had the second highest age-standardized incidence rate at 41.6 (95% CI: 33.8–49.4), annual percentage change showed a gradual but steady increase at 21.7%. Per cancer types, variations in age-standardized incidence rates were noted across age-groups, year-of-presentation, and parishes. Collectively, there was an 8.1% (95% CI: -14.9–37.6) annual percentage change increase in age-standardized incidence rates between 2017 and 2021. Incident cases, age-standardized incidence rates, and trends per cancer type are expected to gradually increase during 2022–2030 (average annual percentage increase is 3.4%). Conclusions This study is a first step in providing reasonable evidence on the incidence, trends, and patterns of four common cancers in Antigua and Barbuda. Female breast and prostate cancers were the dominant cancer types in terms of incidence, age-standardized incidence and predicted increasing incidence trends. Variableness in cancer-specific age-standardized rates across parishes and years of presentation were observed. Besides research, this study has importance for instituting cancer prevention and control measures, including surveillance and healthy lifestyles initiatives.